Selected determinants of spirituality among nurses - Deluga, Alina; Dobrowolska, Beata; Jurek, Krzysztof; Nowicki, Grzegorz; Ślusarska, Barbara (Nursing in the 21st Century, 2021)
SELECTED DETERMINANTS OF SPIRITUALITY AMONG NURSES Introduction. Spirituality has a multi-dimensional nature which influences the professional activities of nurses in a caring profession. Aim. Identifying selected determinants of spirituality among nurses and their relationship with socio-demographic factors. Material and methods. Research was conducted in 2018 on 144 nurses. All of the respondents were active in their profession. The research was made with diagnostic survey method using standardized research tools, including a Self-Description Questionnaire (SDQ), the Spiritual Transcendence Scale (STS), and the Brief Religious Coping (RCOPE) questionnaire, (BR). Results. It was established that age and professional seniority positively correlate with Religious Attitude (SDQ), p<0.05; Transcendence Proper (STS), p<0.01; and with positive religious stress-coping strategies (BR), p<0.01. It shows that a declaration of relationship to faith positively correlates with the subscales of the questionnaire (SDQ), i.e. Religious Attitude (r=0.247, p<0.01), Ethical sensitivity (rho=0.230, p<0.01), and Harmony (r=0.218, p<0.05). Moreover, a strong correlation was confirmed with Transcendence Proper (STS), r=0.40, p<0.01, and with positive religious strategies for coping with stress (BR), r=0.505, p<0.01, and declared relationship to faith. Conclusions. The dimensions of spirituality are significantly related to age, seniority, declaration of attitude to faith, and positive religious stress-coping strategies. Predictors of spirituality among nurses are place of residence, spiritual openness and negative religious stress-coping strategies.